Trees under Agroforestry: An Analysis of Farmers’ Preferences for Tree Species (Indian Journal of Extension Education, 2013)
Present investigation revealed the farmers preferences for trees in agroforestry and relationship between age, land holding of the farmers with trees preferences. The total numbers of trees available with the respondent farmers are 2950 trees. Out of which 880 trees are planted. On an average every farmer has 46.83 trees. The average numbers of planted and natural trees are 4.67 and 35.08 respectively. Shisham was found to be the first preference of the farmers and then Teak followed by Neem respectively. It was found that the respondent of age group 21-40 years (young), Shisham was the first preference, while Sagon, Neem and Subabul are second, third and fourth choice, respectively. For respondents between 41-60 age group, (middle age) the choice of MPTS was more or less similar to young respondents. The older respondent (61-80 years) preferred Shisham, Sagon, Siris and Butea as their preferences in descending order. The overall preference of MPTS in relation to age was found as Shisham-first, Sagon-second, Neem-third and the Sirisis as fourth choice. The marginal farmers preferred trees in descending order as Shisham, Sagon, Subabul and Eucalyptus. For small farmers the preferences were as Shisham-first, Neem- second, Eucalyptus- third and Teak-fourth. For older farmers the preferences were as Shisham-first, Teak-second, Eucalyptus-third and Neem as fourth choice. The overall preference for MPTS reported as Shisham-first, Teak-second, Eucalyptus-third and Neem as fourth choice. The study found that there was positive correlation (0.95) between holding size of the farmers and the availability of trees in their field. It indicates that higher holding size promote more number of trees with farmers.